Are gender gaps due to evaluations of the applicant or the science? A natural experiment at a national funding agency. Issue 10171 (9th February 2019) - Witteman, Holly O; Hendricks, Michael; Straus, Sharon; Tannenbaum, Cara
Summary: Background: Across countries and disciplines, studies show male researchers receive more research funding than their female peers. Because most studies have been observational, it is unclear whether imbalances stem from evaluations of female research investigators or of their proposed research. In 2014, the Canadian Institutes of Health Research created a natural experiment by dividing investigator-initiated funding applications into two new grant programmes: one with and one without an explicit review focus on the calibre of the principal investigator. Methods: We analysed application success among 23 918 grant applications from 7093 principal investigators in all investigator-initiated Canadian Institutes of Health Research grant programmes between 2011 and 2016. We used generalised estimating equations to account for multiple applications by the same applicant and compared differences in application success between male and female principal investigators under different review criteria. Findings: Overall application success across competitions was 15·8%. After adjusting for age and research domain, the predicted probability of success in traditional programmes was 0·9 percentage points lower for female applicants than male applicants (95% CI 2·0 lower–0·2 higher; odds ratio 0·934, 95% CI 0·854–1·022). In the new programme, in which review focused on the proposed science, the gap remained 0·9 percentage points (3·2 lower–1·4 higher; 0·998, 0·794–1·229). In the new programme with an explicit review focus on the calibre of the principal investigator, the gap was 4·0 percentage points (6·7 lower–1·3 lower; 0·705, 0·519–0·960). Interpretation: Gender gaps in grant funding are attributable to less favourable assessments of women as principal investigators, not of the quality of their proposed research. We discuss reasons less favourable assessments might occur and strategies to foster fair and rigorous peer review. Funding: None.